A validated low carbon office building intervention model based on structural equation modelling. (1st November 2018) - Mafimisebi, I. Blessing; Jones, Keith; Sennaroglu, Bahar; Nwaubani, Sunday
Abstract: Building energy performance in existing stocks via facilities management interventions for low carbon building has become expedient and relevant in global climate change discourse. It has raised the consciousness for the need for a unified decision-support model for Facilities Managers and Owners, which could be used for office buildings across countries in achieving cleaner building energy production and use. This paper aimed at examining the factors that affect office Building Energy Performance; their interdependencies; and identify the critical path for interventions. It filled this gap by presenting a combination of interrelated processes (operations, tactics, and strategies) needed to improve building energy performance, reduce costs and greenhouse gas emissions in buildings for organizations. An online questionnaire survey was used in gathering data on current study model variables from participants of case study office buildings in Nigeria and the UK. Structural Equation Modelling technique was used to examine the factors that contribute to improving the energy performance of heterogeneous office buildings in both countries. The result established a strong correlation among observed variables and constructs and high covariance between constructs. This indicates that dependency and interdependence relationships exist amongst constructs, and in between construct and indicators. The finding reveals that an organization needs Sustainability Policy, Facilities Management and Energy Management as a sub-set of Strategic policy incorporated into its core management policy and operations energy management to achieve low carbon building. It also reveals the most critical pathway in the overall model with Strategic Facilities Management discovered to underpin the optimal performance for office buildings. Highlights: The main finding identified low carbon solutions for BEP that fits into a structural model based on the current study theoretical model. The test of structural relationships (hypotheses) amongst model paths indicated causality and mediations for the structural paths. The current study identified the critical path in the overall BEP model for improving energy performance. It established strong interdependency amongst factors across the four constructs in the mannequin and presented a combination of interrelated processes for improving BEP.